Analis Media Promosi Di Instagram Pada Pohaci Mocktail Bar - Marelino Suherkiwando (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This study aims to analyze promotional media on Instagram at Pohaci Mocktail Bar. The research method used is a qualitative method with content analysis techniques. The research data was obtained from the Pohaci Mocktail Bar Instagram account. The results of the study show that Pohaci Mocktail Bar uses various promotional media on Instagram, such as photos, videos, and stories. The promotional content uploaded by Pohaci Mocktail Bar on Instagram is interesting and informative, and is able to increase brand awareness and engagement with its followers.